Resource-Efficient Gigawatt Water Electrolysis in Germany—A Circular Economy Potential Analysis - Levin Matz; Boris Bensmann; Richard Hanke-Rauschenbach; Christine Minke (Circular Economy and Sustainability, 2024)
Green hydrogen will play a key role in the future energy system. For the production of green hydrogen, an installation of alkaline (AWE) and proton exchange membrane water electrolysis (PEMWE) of several gigawatts per year is projected in the upcoming decades. The development of the hydrogen economy is associated with a great demand for scarce and expensive resources. To reduce resource demand and avoid supply bottlenecks, actions toward a circular economy are required. In the present study, three circular economy actions (repair, reuse, and recycling) are analyzed with regard to AWE and PEMWE installation taking Germany as an example. It is found that, so far, only recycling is a viable strategy for a circular economy. For further analysis, a model is developed to assess the impact of recycling on resource demand for AWE and PEMWE scale-up. Mass flows from end-of-life recycling are intergrated into the model, and their economic value is estimated. The results imply that closed-loop recycling can reduce the cumulated primary resource demand by up to 50% in the long run. However, recycling will first be relevant after 2040, while water electrolysis capacities installed before still depend on primary materials. The outlook on the economic value of the recycling materials indicates a volume of up to 2.15 B € per decade for PEMWE and 0.98 B € per decade for AWE recycling. To realize the potential, a recycling industry specialized for those technolgies considering the whole value chain covering dismantling, collection, and recycling must be introduced.